MYCOTIC EXTRACRANIAL CAROTID ARTERIES ANEURYSMS – SYSTEMATIC REVIEW OF THE LITERATURE - Lima, Pedro (2021)
Introduction: Mycotic extracranial carotid artery aneurysms are extremely unusual, with only around 100 cases published in the literature. They represent a challenge due to delayed presentations, possible catastrophic consequences if left untreated, as well as high morbidity after surgical management. Knowledge about infectious aneurysms on this territory remains limited to case reports. Thus, the authors pretend to present a systematic review on the matter with the intention to open a path to further understanding. Methods: Pubmed and Embase databases were consulted using the keywords “infected aneurysm” and “carotid artery”, including published papers in English to the present date. Papers in other languages and papers which focused results on intracranial locations of the disease were excluded. Pseudoaneurysms following trauma or vascular surgery were not included. Results: Inclusion criteria allowed analysis of 55 papers from 1979-2019 reporting data on 58 patients. Median age was 63 years old (min. 9 months; max.88 years), being 67% male. Among diverse risk factors, nearly 70% presented a previous history of bacterial infection or immunosuppression. The right carotid arteries were affected in 52% of cases. The most usual location was the internal carotid artery (31 cases) followed by the common carotid, almost exclusively near the bifurcation in both groups. Clinical presentation was broad, including neck mass (46%), compression syndromes as Horner syndrome, dysphagia or hoarseness (38%); and stroke/transient ischemic attack (11%). The most common bacteria identified were Staphylococcus aureus (26%), followed by Salmonella spp (19%). Autologous vein graft interposition was the technique used to treat the majority of cases. Carotid ligation, occlusion using detachable coils and stent graft angioplasty were among the applied treatments. Mortality was reported in 7 patients (14%). Conclusion: Mycotic carotid artery aneuryms are rare and demand surgical treatment. Diagnosis can be challenging due to late presentation of neck mass or compression syndromes. Treatment implies inflow restoration and removal of infected tissue, so interposition grafts using autologous conduits remain the preferred strategy. Although endovascular techniques can be used in selected cases, one should remember that prosthetic material can be a nidus for bacterial growth. Morbidity and mortality may be higher than expected due to publication bias.